Mechanical power flow from trunk and lower limb joint power to external horizontal power in the track and field block start - Sado, N.; Yoshioka, S.; Fukashiro, S. (European Journal of Sport Science, 2023)
Sprint start performance is measured as the horizontal external power, the time-average rate of horizontal kinetic energy generation. Although joint powers have been examined, not all segment rotations on which positive powers are exerted necessarily contribute to forward propulsion; details regarding horizontal power remain unclear. Here we show the contributions of segment rotations to the forward and upward propulsion. We calculated the joint power exerted on each segment and the contributions from segment rotations to the normalised average horizontal and vertical external powers (P^horiz and P^vert) during the sprint start by 12 male sprinters. Over half P^horiz (55 ± 6%) is due to the front thigh rotation (0.30 ± 0.04), on which the hip and knee exert positive power. Pelvic rotation does not contribute to P^horiz (0.00 ± 0.01). This highlights the importance of the hip-extensors strength and the need for it accompanied by the lumbar-extensors strength cancelling out the hip-extensors action on the pelvis and promoting hip-extensor-induced thigh rotation. The front thigh rotation decreases P^vert (-0.08 ± 0.02). P^vert is primarily induced by rotations of the thorax (0.04 ± 0.01), lumbar region (0.06 ± 0.02), and pelvis (0.04 ± 0.01). Rotations of the lower-limb segments did not contribute to upward propulsion. Therefore, the front thigh induces downward movement, which is counterbalanced by the trunk segments. We bridge the gap in the current understanding from joint power to P^horiz. We present a case involving segments on which positive joint powers are exerted similarly but play different roles: forward or upward propulsion, thereby providing insights into directional control mechanisms in explosive initiation of motion.